Air force one - Bernstein, Armyan; Petersen, Wolfgang ([S.l.] : Buena Vista International [production company] ; Kuala Lumpur : Berjaya HVN [distributor])
In his most powerful role ever, Harrison Ford is the President of the United States in the must-see blockbuster action thriller of the year
Executive producer, Thomas A. Bliss, Marc Abraham, David Lester ; writer, Andrew W Marlowe ; editor, Richard Francis-Bruce
Harrison Ford, Gary Oldman, Wendy Crewson, PeterGuilfoyle
Keywords: Presidents -- United States -- Drama; Presidential aircraft -- United States -- Drama; Terrorists -- United States -- Drama; Suspense in motion pictures